RNA localization: Making its way to the center stage - Chin, Ashley; Lécuyer, Eric (Biochimica et biophysica acta. General subjects, 2017)
Cells are highly organized entities that rely on intricate addressing mechanisms to sort their constituent molecules to precise subcellular locations. These processes are crucial for cells to maintain their proper organization and carry out specialized functions in the body, consequently genetic perturbations that clog up these addressing systems can contribute to disease aetiology. The trafficking of RNA molecules represents an important layer in the control of cellular organization, a process that is both highly prevalent and for which features of the regulatory machineries have been deeply conserved evolutionarily. RNA localization is commonly driven by trans-regulatory factors, including RNA binding proteins at the core, which recognize specific cis-acting zipcode elements within the RNA transcripts. Here, we first review the functions and biological benefits of intracellular RNA trafficking, from the perspective of both coding and non-coding RNAs. Next, we discuss the molecular mechanisms that modulate this localization, emphasizing the diverse features of the cis- and trans-regulators involved, while also highlighting emerging technologies and resources that will prove instrumental in deciphering RNA targeting pathways. We then discuss recent findings that reveal how co-transcriptional regulatory mechanisms operating in the nucleus can dictate the downstream cytoplasmic localization of RNAs. Finally, we survey the growing number of human diseases in which RNA trafficking pathways are impacted, including spinal muscular atrophy, Alzheimer's disease, fragile X syndrome and myotonic dystrophy. Such examples highlight the need to further dissect RNA localization mechanisms, which could ultimately pave the way for the development of RNA-oriented diagnostic and therapeutic strategies. This article is part of a Special Issue entitled "Biochemistry of Synthetic Biology - Recent Developments" Guest Editor: Dr. Ilka Heinemann and Dr. Patrick O’Donoghue. •RNA localization is a prevalent and functionally important layer of gene regulation.•A complex network of cis- and trans-regulators modulate RNA trafficking.•Nuclear history is important for cytoplasmic targeting of mRNAs.•Several neurological and muscle disorders are associated with alterations in RNA localization.